Preliminary exploration on the dimensions of digital learning agility among teachers in Malaysia - MD Khambar, Mas Nida; Abdullah, Kamilah; Mohd Rosli, Nur Dania; Zakaria, Noor Syamilah; Abd Rahim, Nur Aira; Wong, Su Luan (Asia-Pacific Society for Computers in Education, 2024)
To better understand the dimensions of digital learning agility among teachers, a qualitative study was carried out by analyzing semi-structured interviews with three in-service teachers from Selangor, Malaysia. By thematic analysis, this preliminary study has revealed nine dimensions that shapes the Malaysian teachers’ digital learning agility including speed, flexibility, experimenting, performance risk-taking, interpersonal risk-taking, information gathering, collaborating, feedback seeking, and reflecting. Overall, this study shed insights to the existing body of knowledge of learning enablers that might assist in shaping teachers’ digital learning agility